Waste less time on Facebook — follow Brilliant.
×

solve this

X = 2 + 2^(2/(3 ))+ 2^(1/3) So, x^3-6 x^2+6= ???

Note by Napier Jn
3 years, 8 months ago

No vote yet
2 votes

Comments

Sort by:

Top Newest

Given \(x = 2+\sqrt{2}+\sqrt[2]{2}\Rightarrow (x-2)^3 = \left(\sqrt{2}+\sqrt[2]{2}\right)^3\)

We Get \(x^3 -8-6x(x-2) = 2+2^2+3\times 2 \left(\sqrt{2}+\sqrt[2]{2}\right) = 6+6x\)

Now Solve after that.... Jagdish Singh · 3 years, 8 months ago

Log in to reply

×

Problem Loading...

Note Loading...

Set Loading...